Unique Genomic Alterations of Cerebrospinal Fluid Cell-Free DNA Are Critical for Targeted Therapy of Non-Small Cell Lung Cancer With Leptomeningeal Metastasis - Wang, Yongsheng; Jiang, Feng; Xia, Ruixue; Li, Ming; Yao, Chengyun; Li, Yan; Li, Hui; Zhao, Qi; Shi, Mingke; Yu, Yanzhe; Shao, Yang W.; Zhou, Guoren; et al. (Frontiers in Oncology, 2021)
We reported unique molecular features of cerebrospinal fluid(CSF) of NSCLC patients with leptomeningeal metastasis (LM), suggesting establishing CSF as a better liquid biopsy in clinical practices. We performed next-generation panel sequencing of primary tumor tissue, plasma and CSF from 131 NSCLC patients with LM, and observed high somatic copy number variations (CNV) in CSF of NSCLC patients with LM. The status of EGFR-activating mutations was highly concordant between CSF, plasma, and primary tumors. ALK translocation was detected in 8.3% of tumor tissues, but only 2.4% in CSF and 2.7% in plasma. Others such as ROS1 rearrangement, RET fusion, HER2 mutation, NTRK1 fusion, and BRAF V600E mutation were detected in 7.9% of CSF and 11.1% of tumor tissues, but only 4% in plasma. Our study has shed light on the unique genomic variations of CSF and demonstrated that CSF may represent better liquid biopsy for NSCLC patients with LM.